A Highly Selective Fluorescent Probe for Detection of Hydrogen Sulfide in Living Systems: In Vitro and in Vivo Applications. Issue 41 (29th June 2017) - Reja, Shahi Imam; Sharma, Neetu; Gupta, Muskan; Bajaj, Payal; Bhalla, Vandana; Parihar, Ripu D.; Ohri, Puja; Kaur, Gurcharan; Kumar, Manoj
Abstract: A fluorescein‐based fluorescent probe has been designed and synthesised that selectively detects H2 S in aqueous medium, among various analytes tested. This fluorescein‐based fluorescent probe has also been successfully utilised for real‐time imaging of exo‐ and endogenously produced H2 S in cancer cells and normal cells. Moreover, the probe can also detect H2 S in the rat brain hippocampus at variable depths and in living nematodes. Abstract : Revealing images : A fluorescein‐based fluorescent probe has been designed and synthesized to detect H2 S selectively in aqueous medium containing various analytes (see figure). The probe was also successfully utilized for real‐time imaging of exo‐ and endogenously produced H2 S in cancer and normal cells. Moreover, the probe can also detect H2 S in the rat brain hippocampus at variable depths and in living nematodes.